Islamic Moderation (Islam Wasati): The Way Forward To Counter Radicalism - Akbar, Muhammad Yudi Ali; Hidayati, Maslihati Nur; Ridhwan, Muhammad (RSF Conference Series: Business, Management and Social Sciences, 2023)
This study aims to explain the paradox of the face of Islam known as Rahmatan lil 'alamin on the one hand but indicates with acts of radicalism on the other hand. The rise of violence in the name of religion tarnished the face of Islam, which is famous for its friendship. Islam as a tolerant and peaceful teaching against radical and liberal Islam. This paper aims to reveal the root causes of acts of radicalism in the name of religion and how to solve them. This research uses literature study by searching and formulating several primary texts and supporting texts that rely on the topic, and then we analyze it to conclude the conclusion in the end. From the existing data, the authors found a relationship between religious truth claims and acts of violence that occurred because of them. Then came the discourse of Wasati Islam as a middle way in religion. Therefore, it is necessary to have a comprehensive understanding so there are no misunderstandings in religious thought. Muslims must not be trapped in a narrow understanding and stuck with a model of understanding that makes Muslims undeveloped, even liars who transgress. Muslims must be messengers of mercy to this world with calm and peaceful faces by understanding the Shari'ah framework in implementing it.